(untitled) (Studia Prawnicze / The Legal Studies, 2018)
Celem badań jest ocena sposobu rozumienia znamienia „wiele” zawartego w przepisach art. 115 § 2, 163, 165, 166, 169 § 2 i 300 § 3 kodeksu karnego, które jest poważnym problemem teoretycznym i praktycznym. Znamię to jest różnie rozumiane w doktrynie i orzecznictwie. Niekiedy stwierdza się, że nie jest możliwe wskazanie konkretnej liczby, lecz określenie wielości następuje w nawiązaniu do konkretnego stanu faktycznego. W nieostrym znamieniu „wiele” widać element luzu decyzyjnego wprowadzonego decyzją ustawodawcy. Inni autorzy dostrzegają potrzebę ustawienia granic dla znamienia „wiele”, wskazując najczęściej na konieczność interpretowania go w związku z liczebnikiem „kilka”. Badania są próbą weryfikacji tych stanowisk przy zastosowaniu metody formalno-dogmatycznej analizy przepisów kodeksu karnego. The purpose of the study is to analyze the way of understanding the meaning of the “many” mark appearing in the provisions of art. 115 § 2, 163, 165, 166, 169 § 2 and 300 § 3 of Penal Code, which is real theoretical and practical problem. It is variously understood in doctrine and jurisprudence. Sometimes it is indicated that it’s not possible to determine a specific number, but the evaluation of the multiplicity takes place in relation to a specific factual situation, seeing in the out of focus the “many” element of decision-making slack introduced by the decision of the legislator. Other authors recognize the need to set the “many” boundary with the most often indicated in relation to the interpretation of the numeral “several”. The research is attempt to verify these positions using the formal-dogmatic method of analyzing the provisions of the penal code.